PENGEMBANGAN SUBJECT SPECIFIC PEDAGOGY TEMATIK-INTEGRATIF BERBASIS SOSIOKULTURAL BAGI KELAS IV SDN BABARSARI KABUPATEN SLEMAN - Florianus Dus Arifian (PGSD UNIKA SANTU PAULUS RUTENG, 2017)
This study aims at producing thematic-integrative SSP through sociocultural perspective which is appropriate and effective. This study used design of Borg and Gall modified by Sukmadinata into three phases: (1) preliminary study, (2) the development of the model, and (3) testing model.The setting of research is at SDN Babarsari Sleman Regency. The research subjects include the fourth grade students and the teacher.In the preliminary studies, the data were obtained from interview and questionnaire, while at the stage of development model, the data were obtained from validation, questionnaire, and observation.At the stage of test model, the data were gathered from the test and analyzed by T test with a confidence interval of 95%.The results show that the SSP is effective in increasing learning achievement.This was proved by the average result of post-test is higher for the students who were treated by the traditional SSP than those using the learning materials from the Center of Curriculum 2013. The Significant difference in the T value is 3.73 with 31 degree of freedom and the two-tailed significance stands at 0.001.